Controlling Listeria monocytogenes Scott A on Surfaces of Fully Cooked Turkey Deli Product Using Organic Acid-Containing Marinades as Postlethality Dips - Gerardo Casco; Jennifer L. Johnson; T. Matthew Taylor; Carlos N. Gaytán; Mindy M. Brashears; Christine Z. Alvarado (International Journal of Food Science)
This study evaluated the efficacy of organic acids applied singly or in combination as postlethality dips to sliced uncured turkey deli loaves to inhibit the growth of Listeria monocytogenes (Lm) Scott A. Treatments consisted of sodium lactate (SL; 3.6%), potassium lactate (PL; 3.6%), sodium citrate (SC; 0.75%), a combination of SL and sodium diacetate (SDA; 0.25%), and a combination of SL/PL/SDA, alongside appropriate negative and positive controls. Products were inoculated with 104–105 CFU/mL streptomycin-resistant (1500 μg/mL) Lm Scott A prior to treatment. Products were then stored at ~4°C and sampled at 0, 7, 14, 21, 28, 42, and 56 d. The SL/SDA combination applied to turkey slices extended the lag phase through 21 days of refrigerated storage. Numbers of Lm Scott A rose by 0.7 log10 CFU/g through the 56 d storage period. The application of the SL/PL/SDA treatment to turkey product surfaces extended the lag phase through 42 d, with pathogen numbers declining after 21 d. Combination organic acid dips prolonged the lag phase for 2 to 6 wk on turkey product surfaces and can be useful as antimicrobial agents for Lm control on postlethality exposed sliced deli products.